Palatogingival groove and root canal instrumentation - Pinheiro, T. N.; Cintra, L. T.A. [UNESP]; Azuma, M. M.; Benetti, F. [UNESP]; Silva, C. C. [UNESP]; Consolaro, A. (Wiley, 2020)
Aim: To evaluate the morphology and impact of root canal preparation in maxillary incisors with palatogingival grooves (PGG). Methodology: Twenty extracted human maxillary incisors with PGG were subjected to macroscopic analysis and scanning electron microscopy analysis (SEM). The following characteristics of the PGG were evaluated: depth, point of origin in the cingulum, extension and position on the lingual surface. Furthermore, the presence of calculus, communications between the root canal system and the PGG, and root resorptions were investigated. The root canals were subsequently instrumented with K-files of three consecutive sizes. The teeth were sectioned, and the axial plane of each tooth section was imaged using SEM before and after instrumentation. The distance between the root canal walls and the PGG was calculated according to the location. Additionally, the distance between canal walls and cementum was measured at three different sites, to verify if instrumentation influenced dentine removal on a specific wall in teeth with PGG. Statistical analysis was performed using the Mann–Whitney or Student’s t-test (P < 0.05). Results: Macroscopic analysis revealed that a deep groove was most frequently observed (75%), followed by a depression/shallow groove (25%) (P < 0.05). PGG typically originated in the distal margin ridge of the cingulum (65%) (P < 0.05), extending only to the middle (45%) or up to the apical (50%) third of the root (P < 0.05). Additionally, PGGs were typically located on the distal aspect of the lingual surface (70%) (P < 0.05). Calculus was concentrated on the surface of the crown and cementum–enamel junction (P < 0.05). Communication between the root canal and PGG was present in 35% of teeth, and root resorptions were noted in 50% of teeth. The distance between the external root surface and the pulp cavity was significantly narrower after instrumentation (P < 0.05); however, root canal preparation did not influence dentine removal on the specific wall associated with the groove (P > 0.05). Conclusions: Palatogingival grooves were characteristically deep and originated from the distal margin of the cingulum. Although it has been associated with a thinner root wall, root canal preparation did not influence the thickness of the specific wall in the maxillary incisors with PGG.
Keywords: dental morphology; palatogingival groove; root canal treatment; scanning electron microscopy (SEM)